Unraveling the Capacitive Charge Storage Mechanism of Nitrogen-Doped Porous Carbons by EQCM and ssNMR - Zhang, En; Wu, Yih-Chyng; Shao, Hui; Klimavicius, Vytautas; Zhang, Hanyue; Taberna, Pierre-Louis; Grothe, Julia; Buntkowsky, Gerd; Xu, Fei; Simon, Patrice; Kaskel, Stefan (Journal of the American Chemical Society, 2022)
Fundamental understanding of ion electroadsorption processes in porous electrodes on a molecular level provides important guidelines for next-generation energy storage devices like electric double layer capacitors (EDLCs). Porous carbons functionalized by heteroatoms show enhanced capacitive performance, but the underlying mechanism is still elusive, due to the lack of reliable tools to precisely identify multiple N species and establish clear structure property relations. Here, we use advanced analytical techniques such as low-temperature solid-state NMR (ssNMR) and electrochemical quartz crystal microbalance (EQCM) to relate the complex nitrogen functionalities to the charging mechanisms and capacitive performance. For the first time, it is demonstrated at a molecular level that N-doping strongly influences the electroadsorption mechanism in EDLCs. Without N-doping, anion (SO42-) adsorption-desorption dominates the charging mechanism, whereas after doping, Li+ electroadsorption plays a key role. With the help of EQCM, it is demonstrated that SO42- is strongly immobilized on the N-doped surface, leaving Li+ as the main charge carrier. The smaller size and higher concentration of Li+ compared to SO42- benefit a higher capacitance. Amine/amide N is responsible for high capacitance, but surprisingly the pyridinic, pyrrolic, and graphitic N groups have no significant influence. 2D 1H-15N NMR spectroscopy indicates that the conversion from pyridinium to pyrrolic N gives rise to a slightly decreased capacitance. This work not only demonstrates ssNMR as a powerful tool for surface chemistry characterization of electrode materials but also uncovers the related charging mechanism by EQCM, paving the way toward a comprehensive picture of EDLC chemistry.
CRIS-Team Scopus Importer:2023-03-20